Interpersonal Dynamics in Legal Services: A Study of User Perceptions on Court Personnel Communication Skills - Palapah, Maya Amalia Oesman; Hernawati, Riza; Suherman, Maman (UPT Publikasi Ilmiah Unisba, 2024)
Interpersonal communication plays a pivotal role in public services. Despite technology transforming the way we interact with customers and users, human relationships in public services remain crucial. Interpersonal communication also enables direct feedback, which is invaluable for enhancing service quality as it requires honesty and transparency. This study aims to assess the quality of interpersonal communication within public service delivery, particularly focusing on court services. The goal is to ensure that courts can consistently provide the best service to their users' needs. The descriptive method was employed, and data were collected through questionnaires distributed to lawyers as service users, providing valuable insights.. This research shows the excellent interpersonal communication skills exhibited by service personnel towards users, effectively serving the community. These findings are expected to serve as a guideline for other governmental agencies in executing inclusive and competitive public services.